2022
DOI: 10.1136/bmjopen-2021-052320
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary carotenoid intakes and the risk of asthma in adults: a cross-sectional study of NHANES, 2007–2012

Abstract: ObjectiveTo investigate the association between dietary carotenoid intake and asthma using data from a nationally representative sample of US adults.DesignCross-section study.SettingThe National Health and Nutrition Examination Survey 2007–2012.ParticipantsA total of 13 039 participants aged 20–80 years (current asthma n=1784, non-current asthma n=11 255) were included in this study.Primary and secondary outcome measuresAsthma was defined by self-report questionnaires. Weighted logistic regression analyses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Regarding the associations between income level and carotenoid intake, although data are still scarce, similar results were reported. Adults from NHANES [ 32 ] with higher income had greater total carotenoid intake than their counterparts (2.2 and 2.8 μg/ kg per day, respectively), and in the American cohort SELF, β -carotene and lycopene intake was positively associated with household income [ 33 ]. Socioeconomic status was also positively associated with plasma concentrations of lutein/zeaxanthin, lycopene, α - and β -carotene in the Australian cohort DRUID [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the associations between income level and carotenoid intake, although data are still scarce, similar results were reported. Adults from NHANES [ 32 ] with higher income had greater total carotenoid intake than their counterparts (2.2 and 2.8 μg/ kg per day, respectively), and in the American cohort SELF, β -carotene and lycopene intake was positively associated with household income [ 33 ]. Socioeconomic status was also positively associated with plasma concentrations of lutein/zeaxanthin, lycopene, α - and β -carotene in the Australian cohort DRUID [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were classified as having asthma if they met any of the following requirements: 1) previously diagnosed with asthma [ 19 ], 2) using antiasthmatic medication, or 3) taking medications such as selective phosphodiesterase-4 inhibitors, mast cell stabilizers, leukotriene modifiers, or inhaled corticosteroids, were under 40 years old, and had no history of smoking, chronic bronchitis, or emphysema [ 28 , 29 ]. As of December 31, 2019, mortality is calculated by comparing National Death Index (NDI) records with data from the study population's death certificates to identify those who passed away during the study [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Carotenoids have been linked to both the growth inhibition and prevention of cancer, eye disorders, and diabetes in numerous studies [ 17 , 18 ]. A cross-sectional study yielded results indicating an association between higher dietary intake of carotenoids and a lower prevalence of asthma among adults [ 19 ]. Moreover, two separate studies conducted on pediatric populations also demonstrated analogous outcomes, further strengthening the observed relationship [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smokers with low dietary vitamin C (VC) intake had chronic bronchitis symptoms associated with asthma compared with those who had higher intake [ 32 ]. According to quartiles of carotenoid dietary/supplement intake (carotene, lycopene, and lutein with zeaxanthin), the risk of asthma was reported to be lower in the fourth quartile (≥165.59 μg/kg per day) than the first quartile (<41.43 (μg/kg per day) among current smokers, ex-smokers, and nonsmokers with asthma [ 33 ]. One trial revealed no effects of 6 weeks of supplemental vitamin E (VE) on AHR in nonsmokers with asthma [ 34 ].…”
Section: Antioxidant Intake and Asthma In Relation To Smoking Statusmentioning
confidence: 99%